Characterization of exercise-induced hemolysis in endurance horses - Pakula, Patrycja D.; Halama, Anna; Al-Dous, Eman K.; Johnson, Sarah J.; Filho, Silvio A.; Suhre, Karsten; Vinardell, Tatiana (Frontiers in Veterinary Science, 2023)
Exercise-induced hemolysis occurs as the result of intense physical exercise and is caused by metabolic and mechanical factors including repeated muscle contractions leading to capillary vessels compression, vasoconstriction of internal organs and foot strike among others. We hypothesized that exercise-induced hemolysis occurred in endurance racehorses and that its severity was associated with the intensity of exercise. To provide further insight into the hemolysis in endurance horses we deployed a strategy for small molecules (metabolites) profiling, metabolomics, beyond standard molecular methods. The aim of this study was to scrutinize hemolysis parameters, including hemoglobin, haptoglobin, heme, biliverdin, bilirubin, as well as macroscopical plasma color change. The study included 47 Arabian endurance horses competing for 80, 100 and 120 km distances. Blood plasma was collected before and after the competition and analyzed macroscopically, by ELISA and non-targeted metabolomics with liquid chromatography–mass spectrometry. A significant increase in all hemolysis parameters was observed after the race, and an association was found between the measured parameters, average speed and distance completed. Levels of hemolysis markers were highest in horses eliminated for metabolic reasons in comparison to finishers and horses eliminated for lameness (gait abnormality), which may suggest a connection between intensity of exercise, metabolic challenges, and hemolysis. This indicates that hemolysis may contribute to development of metabolic disorders and toxic effects observed in endurance horses after a race. Utilization of omics methods alongside conventional methods revealed a broader insight into the exercise induced hemolysis process by displaying, apart from commonly measured hemoglobin and haptoglobin, levels of hemoglobin degradation metabolites. Obtained results emphasized the importance of respecting horse limitations in regards to speed and distance which, if underestimated, may lead to severe damages.